Second order parallel tensors on $S$ -manifolds and semi-parallel hypersurfaces of $S$ -space forms - Belkhelfa, M.; Mahi, F. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 515.12 We study a second order parallel symmetric tensor in an $\mathcal{S}$-manifold and we deduce that there is no semi-parallel hypersurface in $\mathcal{S}$-space forms $\widetilde{M}^{2n+s}(c)$ with $c eq s.$